1,4-Bis[(Z)-2-(3-mesityl-3-methylcyclobutyl)-2-(thiosemicarbazono)ethyl] piperazine dimethyl sulfoxide disolvate - Yüksektepe, Ç; Soylu, S; Saraçoglu, H; Çaliskan, N; Çukurovali, A; Yilmaz, I; Kazaz, C (Int Union Crystallography, 2005)
The structure of the title compound, C38H56N8S2 (.) 2C(2)H(6)OS, has been determined by single-crystal diffractometry and is compared with the structures of other compounds containing the thiosemicarbazide group. The structure is stabilized by N - H (. . .) S hydrogen bonding, resulting in the formation of infinite chains parallel to the [010] axis. The thiosemicarbazone group has an E configuration.
Keywords: Derivatives